2012
DOI: 10.1039/c2dt30937h
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(ii) driven self-assembly of a saturated quadruple-stranded metallo helicate

Abstract: Complexation of the bridging bidentate ligand N,N'-(pyridine-2,6-diyl)dinicotinamide, L with palladium(II) resulted in a single discrete M(2)L(4) self-assembly, 1, in a quantitative manner. The entropically-controlled assembly of 1 resulted in a rare saturated, quadruple-stranded metallo-helicate, in which both the left-handed (M) and right-handed (P) helicates exist in the crystal structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The bidentate ligand L3 possesses a central aromatic spacer and two terminal 3-pyridyl moieties connected by ester linkages. A few ligands of comparable designs with amide linkages are known, which form [Pd 2 L 4 ] complexes [45][46][47] . The amide linkages are somewhat rigid and are capable of interacting with counteranions inside the corresponding cavity, when suitably oriented thereby influencing the formation of smaller [Pd 2 L 4 ] complexes.…”
Section: Resultsmentioning
confidence: 99%
“…The bidentate ligand L3 possesses a central aromatic spacer and two terminal 3-pyridyl moieties connected by ester linkages. A few ligands of comparable designs with amide linkages are known, which form [Pd 2 L 4 ] complexes [45][46][47] . The amide linkages are somewhat rigid and are capable of interacting with counteranions inside the corresponding cavity, when suitably oriented thereby influencing the formation of smaller [Pd 2 L 4 ] complexes.…”
Section: Resultsmentioning
confidence: 99%
“…23 However, rather than a single product, a mixture of hetero-ligand rhomboid and homo-ligand triangles and other higher order polygons was observed. It was found that this could be overcome by using the tris(terpy) ligand L 35 ; reaction with L 33 and Zn 2+ in a ratio of 1 : 1 : 1.5 gave selectively [Zn 6 (m-Z 3…”
mentioning
confidence: 99%
“…Inspired by our previous progress on synthesis of self‐assembled binuclear complexes,,,,,, we envisioned that the introduction of the 4,4′‐diphenylmethane moiety as spacer into a ligand back‐bone would end up self‐assembled complexes with large cavities. For this purpose, we considered a “C‐shaped” lengthy bidentate pyridine appended ligand, L containing two urea functionalities and a central 4,4′‐diphenylmethane spacer, (Scheme ).…”
Section: Resultsmentioning
confidence: 99%